Предмет: Математика,
автор: arka25
6. Упростите выражение:
А) 5(2х - 3) -6(-5 + 3x)
Б) (6x - 9) + 3(2x+5) -х – 6
Пожалуйста помогите
Ответы
Автор ответа:
1
Пошаговое объяснение:
arka25:
А не подходит
Автор ответа:
1
Ответ:
Пошаговое объяснение:
А) = 10х - 15 + 30 - 18х = -8х + 15
Б) = 6х - 9 + 6х + 15 - х - 6 = 11х
Похожие вопросы
Предмет: Русский язык,
автор: Diana0931
Предмет: Русский язык,
автор: Luissa1
Предмет: Английский язык,
автор: Аноним
Предмет: Химия,
автор: girlschool89
Предмет: Математика,
автор: mila1398